2021
DOI: 10.1186/s12917-021-03019-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parity order on performance, metabolic, and hormonal parameters of grazing beef cows during pre-calving and lactation periods

Abstract: Background Metabolic profile evaluation is a tool widely used in ruminant nutrition as metabolic cues that relate nutrition to physiology. Metabolic and hormonal traits change during pre-partum and lactation according to parity in dairy cows, but studies of beef cows under grazing are scarce. The present study aimed to evaluate how metabolic and hormonal traits change over time, their relationship to performance, and determine if these factors differ according to the parity order of grazing bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…Reduced milk protein and total solids for nulliparous cows were expected. They may be explained by the differences in protein metabolic status since nulliparous cows have lower blood albumin and total protein than multiparous beef ( 17 ) and dairy cows ( 34 , 35 ). These differences are even higher when milk components were expressed in kilograms since parities also differ in milk yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced milk protein and total solids for nulliparous cows were expected. They may be explained by the differences in protein metabolic status since nulliparous cows have lower blood albumin and total protein than multiparous beef ( 17 ) and dairy cows ( 34 , 35 ). These differences are even higher when milk components were expressed in kilograms since parities also differ in milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that age and parity order can influence the metabolism and milk production of dairy ( 15 , 16 ) and beef cows ( 6 , 17 ), where primiparous cows display lower milk production and a more unbalanced nutritional status compared to multiparous cows ( 15 , 17 , 18 ). Thus, different equations are needed to predict the milk yield of Nellore cows according to parity order, since they may differ in milk potential.…”
Section: Introductionmentioning
confidence: 99%
“…Calving interval is longer in parity 1 cows compared to parity 2, 3, 4, and 5 which was also observed in dairy cows ( Evans et al, 2006 ; Eastham et al, 2018 ; Atashi et al, 2021 ). Cows experiencing their first calving are not physically or physiologically mature, so are in a different metabolic state than multiparous cows ( Ferreira et al, 2021 ). Longer calving interval may also be due to herd owners calving heifers earlier in breeding season to mature herd, which is a management practice to give parity 1 cows time to heal.…”
Section: Discussionmentioning
confidence: 99%
“…Differences found in total proteins and albumin concentrations according to parity are not related to weaning stress. According to Ferreira et al [ 16 ], parity directly influences all indicators of protein status (i.e., total proteins, albumin, globulins, urea, and IGF-1) in beef cows. Thus, protein concentrations are expected to be lower for primiparous cows, as this category requires nutrients for fetal development, lactation, and continued growth.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is required to understand whether such responses are affected to the same extent when weaning is performed in the conventional way (at 7–8 months of age) and whether they are also influenced by parity. It is known that weaning stress affects the performance of beef cattle [ 15 ], and the metabolic status of the cow is influenced by parity, in which primiparous cows are more impacted by the lactation period, presenting more unbalanced metabolic and hormonal characteristics and lower body condition scores [ 16 ]. Therefore, understanding whether the response to stress in this period will have a negative impact on the productive life of the cow and whether it differs between categories is essential to adopting appropriate management practices aiming at greater animal welfare and productive and reproductive performance.…”
Section: Introductionmentioning
confidence: 99%